Comparative study: Oral mucosal lesions, signs and symptoms in diabetes mellitus patients with end stage renal disease with analogous findings in diabetes mellitus patients with non-end stage renal disease - Balasubramani Senthil; Subramaniam Shanmugam; Somasundaram Elangovan; Ponna Goundar Elumalai Chandramouli; Shanmugam Bhaskaran; Chandrasekaran Ramesh (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of this study is to compare oral signs, symptoms and oral lesions type and prevalence, in end stage renal disease (ESRD) with non-end stage renal disease (NESRD) in diabetes mellitus (DM) patients. Methodology: Two groups of DM patients were studied, Group 1 includes 100 patients with ESRD, who were under hemodialysis therapy, and Group 2 includes100 patients with NESRD whose serum creatinine level is <2.0 mg/dl. The DM status and other laboratory investigations were recorded, with the patients consent and thorough oral examination was performed and the findings were recorded. All the data were entered into Microsoft Excel sheets. Statistical analysis including Pearson's correlation analysis, Chi-square test, and t-test were done using SPSS software SYSTAT version 7.0. Results: On thorough clinical examination, the prevalence of oral lesions was found to be higher in ESRD patients. The most common lesions such as saburral tongue (P ≤ 0.002), petechiae/ecchymoses (P ≤ 0.000), pale mucosa (P ≤ 0.000), stomatitis medicamentosa (P ≤ 0.043) fissured tongue, smooth tongue, candidiasis, dry and fissured lips, angular cheilitis, uremic stomatitis, signs such as uremic fetor (P ≤ 0.000), xerostomia and symptoms like burning tongue, unpleasant taste are noted. Conclusion: The high prevalence of uremic fetor, saburral tongue, pale mucosa, and petechiae/ecchymoses in ESRD patient group can be considered as a possible sign of undiagnosed advanced stage of renal disease in other diabetic patients.